2004
DOI: 10.1029/2004gl020812
|View full text |Cite
|
Sign up to set email alerts
|

Field observation of fluid circulation patterns in a normal fault system

Abstract: [1] Faults are often assumed to be either barriers or conduits for subsurface fluid flow, although they may act as both, depending on the hydraulic architecture of the fault and the direction of flow with respect to the fault plane. Here we use high-resolution (5 Â 5 m spacing) ground temperature measurements to track geothermal discharge in the step-over region of an active échelon normal fault in southeast Oregon. Our analysis demonstrates that the fault acts as a combination conduit-barrier system and revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 17 publications
3
39
0
Order By: Relevance
“…Recent publications have shown that discharge from springs to the north along the Borax Lake fault cools and moves laterally through the shallow subsurface (Fairley and Hinds, 2004b); in the area of the present study, cooling of the spring discharge appears to be accelerated by mixing with cooler, lateral flow from Borax Lake, confining the area of elevated temperatures to a narrow band close to the trace of the fault (Fig. 2).…”
Section: Data Collection and Analysissupporting
confidence: 55%
“…Recent publications have shown that discharge from springs to the north along the Borax Lake fault cools and moves laterally through the shallow subsurface (Fairley and Hinds, 2004b); in the area of the present study, cooling of the spring discharge appears to be accelerated by mixing with cooler, lateral flow from Borax Lake, confining the area of elevated temperatures to a narrow band close to the trace of the fault (Fig. 2).…”
Section: Data Collection and Analysissupporting
confidence: 55%
“…It is known that faults can have twofold hydraulic behaviours (e.g. Haneberg 1995; Fairley & Hinds 2004a; Rowland & Sibson 2004; Bense & Person 2006). On the one hand, damage or deformation zones increase the fault permeability so that the fault can function as a flow conduit.…”
Section: Numerical Modelling Of the Sbgmentioning
confidence: 99%
“…Travertine and wellcemented, matrix-supported clastics are visible at the land surface over much of the trace of the fault, and well-lithified volcanoclastic sediments that probably define the top of the horst block crop out immediately south of the study area. Together, these observations lead Fairley and Hinds (2004b) to estimate the overburden thickness along the trace of the fault to range from 0 to 5 m; however, recent seismic data indicate that as much as 120 m of variably lithified alluvium may overlie the top of the horst. Furthermore, although the change in land surface elevation across the fault is less than 3 to 4 m, recent geophysical data imply displacement across the fault may be as much as 400 to 500 m.…”
Section: Geological Settingmentioning
confidence: 99%
“…Approximately 175 visible geothermal springs discharge over the~1 km trace of the fault, providing a unique opportunity to examine fault hydraulic architecture in an active, fault-controlled flow system. We use a geostatistical analysis because it allows the development of a quantitative, probabilistic model of heterogeneity; a deterministic model of fault heterogeneity based on exhaustive temperature sampling in the Borax Lake fault is also available (Fairley and Hinds, 2004b), but high-resolution sampling of this type is generally only practical within a spatially restricted area. The analysis presented below offers an approach to evaluating fault hydrology at the site scale that compliments the methods described above, and provides a useful tool for testing conceptual models of fault hydraulic architecture.…”
Section: Introductionmentioning
confidence: 99%